2018
DOI: 10.1007/s00012-018-0526-8
|View full text |Cite
|
Sign up to set email alerts
|

Infinitely many reducts of homogeneous structures

Abstract: It is shown that the countably infinite dimensional pointed vector space (the vector space equipped with a constant) over a finite field has infinitely many first order definable reducts. This implies that the countable homogeneous Boolean-algebra has infinitely many reducts. Our construction over the 2-element field is related to the Reed-Muller codes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This conjecture has been verified for numerous structures including the order of the rationals [14] and the random graph [20], but is still open [21,4,16,9,18,17,10,8,1,19,2,7,6,11]. For countable homogeneous structures in a finite non-relational signature, it turns out to be false: the countable vector space over the two-element field, with an additionally distinguished non-zero vector, has an infinite number of first-order reducts [12], although it has only finitely many (four) first-order reducts if it is not equipped with any additional structure beyond the vector space structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…This conjecture has been verified for numerous structures including the order of the rationals [14] and the random graph [20], but is still open [21,4,16,9,18,17,10,8,1,19,2,7,6,11]. For countable homogeneous structures in a finite non-relational signature, it turns out to be false: the countable vector space over the two-element field, with an additionally distinguished non-zero vector, has an infinite number of first-order reducts [12], although it has only finitely many (four) first-order reducts if it is not equipped with any additional structure beyond the vector space structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…The list includes the rationals with the usual ordering [25], the countably infinite random graph [37], the homogeneous universal -free graphs [38], the expansion of by a constant [31], the universal homogeneous partial order [35], the random ordered graph [19], and many more [1, 2, 12, 13]. Note that if we drop the assumption that the signature of the homogeneous structure is relational, then Thomas’ conjecture is false even if we keep the assumption that is -categorical: already the countable atomless Boolean algebra has infinitely many first-order reducts [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent work gives evidence that the conjecture is false. In [8], it is shown that the countable homogeneous Boolean-algebra has infinitely many reducts. (This is not a counter-example to Thomas' Conjecture because the structure is homogeneous in a functional language, not a relational one.)…”
mentioning
confidence: 99%